Types of Feeding and Presence of Harmful Oral Habits in Children with Cleft Lip and/or Palate: A Pilot Study - Kriss Melani Sanga Gárate; Mariana Leonel Martins; Gloria Fernanda Barbosa de Araújo Castro; Beatriz Costa (Association of Support to Oral Health Research (APESB), 2022)
Objective: To verify the relationship between the types of feeding and presence of harmful oral habits (HOH) in children with cleft lip (CL), palate (CP) and cleft lip and palate (CLP), as well as to compare the different types of cleft to each other. Material and Methods: A form was applied to the parents of 162 children (3-5 years old), addressing the following variables: gender, cleft type, age, socioeconomic conditions, type of breastfeeding, presence of HOH, and the parents' knowledge about the consequences of oral habits. The data obtained were analyzed by chi-square test (p<0.05). Results: The majority of children (83.3%) were bottle-fed and 12.3%  were exclusively maternal breastfed. The main reason for weaning was the presence of cleft (59.9%). Breastfeeding was significantly higher in children with CL (75%) in comparison with CP (20%) and CLP (5%) (p<0.001). Children with CLP were 12 times more likely to be bottle-fed than children with CL (OR=12.21; CI=4.09-36.45). The prevalence of HOH was 37%. Sociodemographic characteristics were not associated with the presence of HOH (p>0.05). The type of feeding and cleft were not decisive to present some type of HOH (p>0.05) and 87% of parents stated that HOH could lead to serious complications of tooth misalignment. Conclusion: The type of feeding and fissure did not determine the acquisition of harmful oral habits in children with cleft. However, the greater the fissure's complexity, the lesser the chance of children receiving exclusive breastfeeding.